Nlrx1-Regulated Defense and Metabolic Responses to Aspergillus fumigatus Are Morphotype and Cell Type Specific - Kastelberg, Bridget; Ayubi, Tariq; Tubau-Juni, Nuria; Leber, Andrew; Hontecillas, Raquel; Bassaganya-Riera, Josep; Kale, Shiv D. (Frontiers in Immunology, 2021)
The Nlr family member X1 (Nlrx1) is an immuno-metabolic hub involved in mediating effective responses to virus, bacteria, fungi, cancer, and auto-immune diseases. We have previously shown that Nlrx1 is a critical regulator of immune signaling and mortality in several models of pulmonary fungal infection using the clinically relevant fungus Aspergillus fumigatus. In the absence of Nlrx1, hosts produce an enhanced Th2 response primarily by CD103+ dendritic cell populations resulting in enhanced mortality via immunopathogenesis as well as enhanced fungal burden. Here we present our subsequent efforts showcasing loss of Nlrx1 resulting in a decreased ability of host cells to process A. fumigatus conidia in a cell type specific manner for BEAS-2B airway epithelial cells, alveolar macrophages, bone marrow derived macrophages, but not bone marrow derived neutrophils. Further, loss of Nlrx1 results in a diminished ability to generate superoxide and/or generic reactive oxygen species during specific responses to fungal PAMPs, conidia and hyphae. Analysis of glycolysis and mitochondrial function suggests Nlrx1 is needed to appropriately shutdown glycolysis in response to A. fumigatus conidia and increase glycolysis in response to hyphae in BEAS-2B cells. Blocking glycolysis and PPP via 2-DG and NADPH production through glucose-6-phosphate dehydrogenase inhibitor resulted in significantly diminished conidial processing in wildtype BEAS-2B cells to the levels of Nlrx1 deficient BEAS-2B cells. Our findings suggest a need for airway epithelial cells to generate NADPH for reactive oxygen species production in response to conidia via the pentose phosphate pathway (PPP). In context to fungal pulmonary infections, our results show Nlrx1 plays significant roles in host defense via modulation of several aspects of metabolism, particularly glycolysis, to facilitate conidia processing in addition to its critical role in regulating immune signaling.